Vanadium-based highly active and selective catalysts for oxidative dehydrogenation of ethyl lactate to ethyl pyruvate - Doke, Dhananjay; Khomane, Sonali B.; Pandhare, Swati; Dongare, Mohan K.; Dumeignil, Franck; Umbarkar, Shubhangi (Applied Catalysis A: General, 2019)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Pyruvates are important intermediates for various bioactive and pharmaceutical molecules. Synthesis of pyruvates is challenging due to low selectivity, as the pyruvates are prone to polymerisation. In the present work, oxidative dehydrogenation of ethyl lactate to ethyl pyruvate was carried out under very mild conditions using vanadium-based homogeneous and heterogeneous catalysts in the presence of aqueous <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">t<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">-butyl hydroperoxide as an oxidant. Homogenous vanadium-based catalyst, VO(acac)<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> in acetonitrile solvent, gave excellent conversion (upto 83%) with 100% selectivity to ethyl pyruvate at room temperature. However, the heterogeneous catalyst, V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> exhibited very high activity for oxidative dehydrogenation of ethyl lactate only at higher temperature (80 °C). At higher temperature, significant TBHP decomposition was observed if all TBHP was added in one lot. In case of ethyl lactate dehydrogenation using V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst at 80 °C with two equivalents TBHP, 60% ethyl lactate conversion with 100% TBHP conversions were observed after 5 h when all TBHP was added initially in the reaction mixture. However, the ethyl lactate conversion at 80 °C, after 5 h increased to 72% when the same amount of TBHP was added batch wise over a period of 4 h, indicating improved conversion of TBHP to ethyl pyruvate. The heterogeneous catalyst, V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> exhibited up to 98% conversion with 100% ethyl pyruvate selectivity at 80 °C after 10 h with 3 equivalent TBHP added batch wise. The homogeneous catalyst could not be reused while V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> could be successfully recycled five times without catalytic performances loss. Oxidation proceeds by radical mechanism, as proved by experiment with radical scavenger.

Efficient cascade C-N coupling reactions catalyzed by a recyclable MoOx/ Nb2O5 nanomaterial for valuable N-heterocycles synthesis - Singh, Nittan; Kalbande, Pavan Narayan; Umbarkar, Shubhangi; Sudarsanam, Putla (Molecular Catalysis, 2022)
The efficient cascade synthesis of pharmaceutically valuable N-heterocycles at solvent-free conditions was achieved using a robust, recyclable MoOx/Nb2O5 nanocatalyst. The results of catalyst screening revealed that the MoOx/Nb2O5 nanorods, calcined at 500 degrees C (MoNb5), exhibit excellent catalytic activity in the oxidative coupling of benzylamine with 96.5% conversion and >99.6% selectivity to the desirable imine product. The uniform dispersion of Mo-oxide nanoparticles (average particle size: 5.2 +/- 0.5 nm) on shape-controlled Nb2O5 nanorods (width: 5.3 +/- 0.5 nm and length: 23-38 nm) in MoNb5 catalyst led to improved structural and acid properties, beneficial for the cascade C-N bond construction. The shape-controlled MoNb5 catalyst showed versatile activity in various cascade C-N coupling reactions to obtain 2-phenylbenzimidazole, 2-phenyl-quinaxoline, and 2-phenyl-2,3-dihydroquinazolin-4(1H)-one with good to excellent yields at solvent-free con-ditions. The optimum ratio of Lewis/Bronsted acid sites, the unique structure of Nb2O5 nanorods, and the strong MoO3-Nb2O5 interaction are the key reasons for the higher activity of MoNb5 catalyst. The efficient reusability of MoNb5 catalyst, its remarkable activity in diverse N-heterocycles synthesis, and efficient gram-scale synthesis emphasize its practical application for the cascade C-N coupling reactions under benign conditions.
Keywords: Acid sites optimization; Cascade C-N bond formation; Diverse nitrogenous chemicals; Heterogeneous nanosized catalyst; MoO3-Nb2O5 interaction; Nb2O5 nanorods

One-pot synthesized efficient molybdenum-niobium-oxide nanocatalyst for selective C-O and C-N coupling reactions at mild conditions - Kalbande, Pavan Narayan; Singh, Nittan; Swapna, Bhattu; Umbarkar, Shubhangi; Sudarsanam, Putla (Catalysis Communications, 2023)
An efficient molybdenum-niobium-oxide nanomaterial was synthesized by a one-pot hydrothermal method for selective C-O (glycerol ketalization) and C-N coupling (benzylamine oxidation) reactions. The catalytically favourable properties, such as defective metal sites, truncated surfaces, and uniform metal dispersion in the MoO3-Nb2O5 nanorods, calcined at 500 degrees C (MoNb OPS-5), were confirmed by Raman, HR-TEM, and STEM-EDX, respectively. Because of improved Lewis/Bronsted acidic strength, the MoNb OPS-5 catalyst showed higher activity in glycerol ketalization and benzylamine oxidation at mild conditions, giving superior selectivity to solketal (97%) and dibenzylimine (99%), respectively. The MoNb OPS-5 catalyst showed high structural stability and considerable good reusability efficacy.
Keywords: C-O and C-N coupling; Glycerol and benzylamine; Mo-Nb-O nanocatalyst; nanocatalysts; One-pot hydrothermal synthesis

An effective, facile, and rapid synthesis of nanosized Mn3O4 using a microwave route - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Kamble, Aditi; Vaishnav, Vishal; Bogalera, Shivamurthy P.; Manikandan, Marimuthu; Nayaka, Girish Praveen; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Nanoparticle Research, 2024)
Microwave-assisted one-pot, one-step, calcination-free synthesis of nanosized Mn3O4 is reported using only benzylamine and manganese acetate. Benzylamine in this protocol plays a vital role for efficient microwave synthesis. This microwave method enables the synthesis of nanosized Mn3O4 in just few hours only in a single step eliminating the need of calcinations of any intermediate. The synthesized nanosized Mn3O4 was analyzed by XRD, HRTEM, EDAX, and Raman spectroscopy. The catalytic and electrochemical properties of as-synthesized Mn3O4 were investigated. In galvanostatic charge-discharge experiments, after 800 cycles, more than 89% capacitance was retained for electrodes made by as synthesized Mn3O4 nanomaterials indicating its very good stability. In the catalytic conversion of cinnamyl alcohol to cinnamaldehyde via oxidation, using as prepared nanosized Mn3O4 as a catalyst, it displays effective catalytic properties. A probable mechanical study of its formation was also envisaged. This synthesis protocol is additive-free, occurs in a short time, is facile, is energy efficient, and eliminates the use of many chemicals. These silent features make these reported protocols economically viable and environmentally benign which adhere to the principles of Green Chemistry.
Keywords: Calcination free; Electrochemical and catalytic properties; Nanosized Mn3O4; Single-step synthesis

Facile and eco-friendly synthesis of Mn2O3 nanoparticles via microwave-assisted glycerol-thermal method - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Gehlot, Bhavika; Kamble, Aditi; Manikandan, Marimuthu; Bhosale, Hritvik; Vaishnav, Vishal; Rathod, Rutik; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Chemical Sciences, 2025)
Microwave-assisted efficient synthesis of nanosized manganese oxide (Mn2O3) is reported using glycerol and manganese acetate. Glycerol in this reported methodology acts as an efficient solvent for this nanomaterial synthesis under microwave radiation. This reported method enables the synthesis of nanosized Mn2O3 without further use of additives, stabilizers, and bases other than glycerol and manganese precursor. Glycerol is a renewable biomaterial derived nonvolatile and nontoxic, safe solvent. It has a high boiling point and dielectric constant, which makes it an ideal solvent for microwave synthesis. The synthesized nanosized Mn2O3 was analyzed by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. We examined the catalytic properties of as-synthesized Mn2O3 for cinnamyl alcohol oxidation to cinnamaldehyde. In this oxidation activity experiment, nanosized Mn2O3 exhibits good conversion and selectivity towards the desired product. We also made an attempt to understand the probable mechanism of nanomaterial formation and found some conclusive evidence to support it. This research methodology is facile, energy efficient, and involves minimum chemicals for synthesis. It makes this reported methodology not only economically attractive but also environmentally friendly, which aligns well with green chemistry principles.
Keywords: Glycerol; green chemistry; Nanosized Mn2O3; nanostructured catalysis